"Una sorta di intelligenza iconica". Immagine e conoscenza intuitiva (Lebenswelt. Aesthetics and philosophy of experience., 2012)
After outlining some theoretical key points in the correspondence between Gottfried Boehm and Thomas Mitchell, this essay aims at examining how the act of seeing can lead to an intuitive form of knowledge. Particular attention will be paid to the concept of «iconic» developed by Max Imdahl and to Robert Rosenblum’s attempt to apply Panofskian iconology to non-objectual art.